Impact of Immigration Policy on future US population size - Philip Cafaro (The Journal of Population and Sustainability)
Immigration will be the key factor determining whether populations in the developed world increase or decrease over the coming century. New policy-based population projections illustrate this for the United States. Expansive immigration policies could increase the US population by hundreds of millions by 2100, while more restrictive policies could lead to population stabilisation or significant reductions. For the US, there is no plausible high-immigration path to a sustainable population. Because larger populations increase human environmental impacts, sustainability advocates in the US and other countries with high net immigration levels have strong prima facie reasons to support immigration reductions. Such reductions could achieve smaller populations in receiver countries and encourage smaller populations in sender countries, contributing to global ecological sustainability.